Optimization of Enzymatic Hydrolysis Process of Morchella esculenta and Analysis of Volatile Flavor Compounds in Enzymatic Hydrolysate - Xiaofeng ZENG; Mi YAN; Zhixing GE; Lunjiang GAO; Xumin YIN; Yuan DIAO; Sang SHANG; Shunde ZENG (Shipin gongye ke-ji)
To optimize the enzymatic hydrolysis process of Morchella esculenta and expore the volatile flavor compounds in its enzymatic hydrolysate, the enzymatic hydrolysis was optimized by response surface design, and the key flavor compounds were identified by headspace-solid phase microextraction-gas chromatography-mass spectrometry (HS-SPME-GC-MS) combined with the odor activity value (OAV). Results indications were as follows: enzyme addition amount of 5000 U/g, pH6.7, enzymolysis temperature at 44 ℃ for 2 h, the hydrolysis degree was 34.11% under the above mentioned conditions and a total of 23 volatile flavor compounds were identified by GC-MS analysis, among which 17 werein blank group and 21 in enzymatic group. After enzymatic hydrolysis process, the content of flavor compounds increased by 203.71%. Aldehydes were the main volatile flavor compounds, accounting for 78.50% of the whole flavor compounds. Compounds with OAV≥1 were further analyzed, including 7 in the blank group and 9 in the enzymatic group. Isovaleraldehyde, phenylacetaldehyde, hexenal, benzaldehyde, nonanal, linalool, 2-amylfuran, limonene and naphthalene were identified as the key flavor compounds in the enzymatic hydrolysate of Morchella esculenta. Enzymatic hydrolysis can promote the release of flavor compounds, thus providing data basis for the flavor utilization, the deep processing and development of seasoning for Morchella esculenta.